4(3x-2)-3=4(x-3)+33

Simple and best practice solution for 4(3x-2)-3=4(x-3)+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-2)-3=4(x-3)+33 equation:


Simplifying
4(3x + -2) + -3 = 4(x + -3) + 33

Reorder the terms:
4(-2 + 3x) + -3 = 4(x + -3) + 33
(-2 * 4 + 3x * 4) + -3 = 4(x + -3) + 33
(-8 + 12x) + -3 = 4(x + -3) + 33

Reorder the terms:
-8 + -3 + 12x = 4(x + -3) + 33

Combine like terms: -8 + -3 = -11
-11 + 12x = 4(x + -3) + 33

Reorder the terms:
-11 + 12x = 4(-3 + x) + 33
-11 + 12x = (-3 * 4 + x * 4) + 33
-11 + 12x = (-12 + 4x) + 33

Reorder the terms:
-11 + 12x = -12 + 33 + 4x

Combine like terms: -12 + 33 = 21
-11 + 12x = 21 + 4x

Solving
-11 + 12x = 21 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-11 + 12x + -4x = 21 + 4x + -4x

Combine like terms: 12x + -4x = 8x
-11 + 8x = 21 + 4x + -4x

Combine like terms: 4x + -4x = 0
-11 + 8x = 21 + 0
-11 + 8x = 21

Add '11' to each side of the equation.
-11 + 11 + 8x = 21 + 11

Combine like terms: -11 + 11 = 0
0 + 8x = 21 + 11
8x = 21 + 11

Combine like terms: 21 + 11 = 32
8x = 32

Divide each side by '8'.
x = 4

Simplifying
x = 4

See similar equations:

| 8m+20=2m | | 8(z-927)=256 | | 24a=6a*4 | | 300=x+75 | | 2y-7/y | | Y-7=14.1 | | 240=x-60 | | 25-6[(2-7)-(-5-7)]= | | 6(2x-5)=5(3x+7) | | 7(4x+1)=5(4x+3) | | 3(5-4x)=3(3x+4) | | 5(X+3)+(2X-7)=3X-9 | | 1/3,47/6 | | 82-k=37 | | x^2-3x+62=0 | | 240=x+75 | | 5x-7=2x-67 | | X+4(4x+16)=21 | | 9(n+1)=3(n-5) | | 4x+50=130 | | (5w-8)(9-w)=0 | | y=x^2-2.4x-2.2 | | -5(-8x+5)+3x=-369 | | (W+2)(w-5)= | | 2y+10=3y | | 0=2w^2-3w-44 | | 8(-8+8k)=-192 | | 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 |

Equations solver categories